A 3D crystal plasticity model of monotonic and cyclic simple shear deformation for commercial-purity polycrystalline Ti with a harmonic structure. (January 2019) - Wang, Xiang; Cazes, Fabien; Li, Jia; Hocini, Azziz; Ameyama, Kei; Dirras, Guy
Highlights: A 3D crystal plasticity model is established for monotonic and cyclic simple shear deformation of pure Ti with a harmonic structure. The crystalline plasticity theory is implemented to model the constitutive behavior of the hexagonal close-packed polycrystals. The grain size effect on the plastic yielding and hardening properties is considered by means of the Hall-Petch relation. A special localization-homogenization procedure is adapted to link the microscopic and macroscopic behaviors; This model is implemented into a finite element code to predict the crystalline plasticity behavior for bimodal HS Ti. Abstract: A micromechanical model was developed to describe the monotonic and cyclic simple shear deformation behavior of commercial-purity polycrystalline titanium (CP-Ti) with a harmonic structure (HS) design. The crystalline plasticity theory was implemented to model the constitutive behavior of the hexagonal close-packed (HCP) polycrystals. The grain size effect on the plastic yielding and hardening properties was considered by means of the classic Hall-Petch relation. Multiscale analyses were carried out for a representative volume element (RVE), including an fine-grained (FG) phase and a coarse-grained (CG) phase. This model was implemented into a finite element code (Cast3M) by means of a user subroutine. Monotonic simple shear tests and cyclic shear tests with imposed increasing strain amplitudes were carried out for CG and HS samples. Comparisons between the numerical results and the experimental data revealed the model's ability to describe the overall response correctly for both the HS CP-Ti and the homogenous CG CP-Ti under monotonic and cyclic shear loading.